2007
DOI: 10.1038/sj.gt.3303020
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis following adeno-associated viral gene expression of human soluble TNF receptor (TNFRII-Fc) in baboon hearts

Abstract: Sequestration of tumor necrosis factor-a (TNFa) by TNFreceptor immunoglobulin G (IgG)-Fc fusion proteins can limit heart failure progression in rodent models. In this study we directly injected an adeno-associated viruses (AAV)-2 construct encoding a human TNF receptor II IgG-Fc fusion protein (AAV-TNFRII-Fc) into healthy baboon hearts and assessed virally encoded gene expression and clinical response. Adult baboons received direct cardiac injections of AAV-TNFRII-Fc (B5 Â 10 12 viral/genomes/baboon) or an equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…2,[8][9][10] However, the systemic perturbation resulting from hydrodynamic injection remains a serious limitation for clinical application, as it can lead to circulatory collapse and even death. To avoid this adverse effect, we have described a retrograde cathetermediated gene delivery procedure 5 with the aim of locally reproducing the intrahepatic conditions mediated by tail vein hydrodynamic injection.…”
Section: Discussionmentioning
confidence: 99%
“…2,[8][9][10] However, the systemic perturbation resulting from hydrodynamic injection remains a serious limitation for clinical application, as it can lead to circulatory collapse and even death. To avoid this adverse effect, we have described a retrograde cathetermediated gene delivery procedure 5 with the aim of locally reproducing the intrahepatic conditions mediated by tail vein hydrodynamic injection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using virus-mediated transfer of shRNA directed against PLB in cardiomyocyte culture have demonstrated that it is an effective method for both knocking down PLB expression and modulating calcium handling (Fechner et al, 2007;Andino et al, 2008), and one study in a rat model of HF demonstrated that AAV-mediated transfer of shRNA is effective in restoring cardiac function and geometry (Suckau et al, 2009). In addition, because the gene product in this case would be a functional RNA and not a mutant protein (dnPLB), this strategy would avoid the potential of evoking a T cell response directed against cells expressing the transgene, as has been reported after AAV-mediated cardiac gene transfer of a modified, soluble TNF receptor in baboons (McTiernan et al, 2007). This is an important consideration when considering large animal and clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Intramyocardial delivery of human soluble tumor necrosis factor-a receptor II-Fc fusion protein was performed in intact non-human primates; however, it was associated with local myocarditis at the injection sites. 94 A unique approach is the gene delivery of neuronal nitric oxide synthase to cardiac vagus in pigs. 95 Because enhanced vagal function was observed after the gene delivery, additional positive data in a heart failure model may hold more promise.…”
Section: Other Gene Targetsmentioning
confidence: 99%